A new and five rare bdelloids from Korea - Song, Min Ok; Lee, Chang-Ho (Zootaxa, 2017)
A taxonomic study on bdelloid rotifers collected from various terrestrial habitats at six different locations in Korea yielded 12 new Korean records and a new species, Philodina koreana n. sp. Among the 12 new Korean records, eight species and two subspecies are new to Asia. These new Asian records include five rare species with poorly known distributions. Philodina childi Milne and P. scabra Milne were rediscovered in Korea almost 100 years after the original descriptions from South Africa. Our study is the first to report Habrotrocha longicalcarata Bērzinš outside its type locality. Macrotrachela nixa Donner has previously been reported only from New Zealand and the Antarctic after description from Spain. Finally, H. solida Donner is recorded outside Europe for the first time. Here, we provide a description of the new species and discuss the taxonomy and distribution of these five rare species. In addition, a partial sequence of mitochondrial cytochrome c oxidase subunit I gene (mtCOX1) for P. koreana n. sp. as well as a taxonomic key for the Philodina species recorded from Korea to date are also provided here.